Modulation of airway hyperresponsiveness by rhinovirus exposure - Lo, Dennis (Respir Res, 2018)
Rhinovirus (RV) exposure has been implicated in childhood development of wheeze evoking asthma and exacerbations of underlying airways disease. Studies such as the Copenhagen Prospective Studies on Asthma in Childhood (COPSAC) and Childhood Origins of ASThma (COAST) have identified RV as a pathogen inducing severe respiratory disease. RVs also modulate airway hyperresponsiveness (AHR), a key characteristic of such diseases. Although potential factors underlying mechanisms by which RV induces AHR have been postulated, the precise mechanisms of AHR following RV exposure remain elusive. A challenge to RV-related research stems from inadequate models for study. While human models raise ethical concerns and are relatively difficult in terms of subject recruitment, murine models are limited by susceptibility of infection to the relatively uncommon minor group (RV-B) serotypes, strains that are generally associated with infrequent clinical respiratory virus infections. Although a transgenic mouse strain that has been developed has enhanced susceptibility for infection with the common major group (RV-A) serotypes, few studies have focused on RV in the context of allergic airways disease rather than understanding RV-induced AHR. Recently, the receptor for the virulent RV-C CDHR3, was identified, but a dearth of studies have examined RV-C-induced effects in humans. Currently, the mechanisms by which RV infections modulate airway smooth muscle (ASM) shortening or excitation-contraction coupling remain elusive. Further, only one study has investigated the effects of RV on bronchodilatory mechanisms, with only speculation as to mechanisms underlying RV-mediated modulation of bronchoconstriction.